Sedimentary model controlled by alternating dry-wet climatic cycles environment of Yanchang Formation and exploration significance in upper Triassic, Ordos basin - Feng, Yingqi; Jiang, Lin; Jiang, Hua; Gao, Yang; Zhao, Wen; Zhang, Tongxi; Hu, Yao (Frontiers in Earth Science, 2025)
The Ordos Basin, one of China’s most significant onshore oil and gas basins, hosts the Triassic Yanchang Formation, renowned for its multi-layered oil production and three-dimensional distribution of diverse hydrocarbon resources. The formation’s abundant crude oil reserves, coupled with the stratified distribution of shale oil, tight oil, and conventional oil, have garnered substantial attention from researchers globally. Understanding the distribution patterns and controlling factors of these reservoirs is crucial for optimizing exploration and development strategies. This study provides a comprehensive analysis of the sedimentary facies within the Yanchang Formation, elucidating the interplay between sedimentary sequences and environmental-climatic changes. It challenges the traditional view that lake-level fluctuations predominantly control reservoir sand body distribution, proposing instead a new sedimentary model driven by the combined effects of tectonic activity and alternating dry-wet climatic conditions. Our findings reveal that the Yanchang Formation’s climate exhibited a tripartite division, with abrupt climatic fluctuations likely influenced by major tectonic events such as those related to the Quinling orogeny such as the Qinling orogeny. The middle Triassic (Chang 10∼Chang 8) and late Triassic (Chang 3∼Chang 1) stages were characterized by arid conditions. During these periods, the eastern basin, with its gentle topography and limited catchment areas, was dominated by flood-driven sedimentation events. In contrast, the steeper western region developed extensive braided river deltas. The middle stage (Chang 7∼Chang 4 + 5), influenced by the Carnian Pluvial Episode (CPE), experienced a humid climate, fostering fluvial, deltaic, lacustrine and gravity flow deposits and the development of high-quality source rocks. Additionally, this study identifies and systematically analyzes sedimentary facies unique to arid environments during low lake-level stages: the fluvial fan system. We define its developmental conditions, distribution patterns, and sedimentary sequence variations in response to climatic changes. This discovery challenges the conventional view that the Yanchang Formation is dominated by shallow-water delta deposits, offering new insights into the sedimentary theory of continental basins and providing valuable guidance for future oil and gas exploration.